Problems Of Implementing Penal Provisions In The Law Of The United Arab Emirates - An Analytical Study - Mohamed Ahmed Ali Ahmed Alhefeiti; Norman Zakiyy Chow Jen-T’chiang; Zulfaqar Mamat (Usuli Faqih Resaerch Centre PLT, 2024)
Vol. 15. No. 1December Issue 2022 Page(117-136)